Spatial patterns of excess mortality in the first year of the COVID19 pandemic in Germany - Thomas Wieland (European Journal of Geography)
In order to quantify the societal impact of the Corona pandemic, several studies have estimated excess mortality rather than infections or COVID-19-related deaths. The question of whether there was excess mortality associated with COVID-19 in Germany in the first year of the pandemic is controversial, as there are different ways of calculating this. From the perspective of health geography, however, this question must be answered with a spatial approach since epidemics are spatial diffusion processes and mortality varies regionally. This study aims to test whether there is excess mortality at a regional level in Germany in 2020, whether it is spatially dependent and whether allcause mortality is associated with COVID-19-related deaths. Excess mortality is investigated at a small-scale spatial level (NUTS 3; 400 counties) and under consideration of demographic changes by calculating Standardized Mortality Ratios (SMRs). SMRs and COVID-19-related deaths per 100,000 people are tested for spatial dependence by the Moran’s I index. It is, furthermore, tested whether all-cause mortality is associated with COVID-19-related deaths by correlation coefficients. Excess mortality can be detected in only a minority of counties, regardless of age group, confirming previous results of no excess mortality overall. However, there are large regional disparities of all-cause mortality and COVID-19-related deaths. In older age groups, both indicators show spatial dependence. These results make it possible to identify COVID19 hotspots. (Excess) mortality in older age groups is impacted by COVID-19, but this association is not found for young and middle age groups.